The novelized assignments for managerial Accounting of creating value to shareholder (Al-Mansour Journal, 2022)
There are certain changes related to the extension of management's assignments to strategic areas which isclosely connected with increasing influence of numerous factors such as the rapid growth of innovation, thecontinuous technical development acceleration, and extension of competition arena among businessorganizations. These changes force management to adopt approaches based on concepts that are characterized bystrategic view. Among these concepts, one can make use of value creation concept.The research aims at presenting and analyzing contemporary approaches based on concepts that provideintellectual bases of strategic view in administrating expected future costs, since the survival and success ofbusiness units constitute a function of the methods of understanding, analyzing, and applying those approachesand concepts which the business units adopt.The research reaches at a number of conclusions concerning the concepts that seek value creation for theshareholder which take the form of either paid dividends or gained capital added to the shareholder's equity, orsometimes, both these forms are adopted.The research points out the importance of these concepts and approaches to support the role of managerialaccounting in terms of using them within the so called framework of "value pyramid". All this should provide avalid basis for the application of value-based management